Investor information gathering and the resolution of uncertainty - Neilson, Jed J. (Journal of Accounting and Economics, 2022)
Information gathering is an instinctive response to uncertainty, but such efforts may not fully resolve the uncertainty that prompted them. This implies that proxies for investor information gathering may endogenously reflect investor uncertainty, not only before but also after information collection. I find evidence consistent with this pattern using data on public internet access of SEC filings around firms’ earnings announcements. My findings suggest that proxies for investor search and information gathering can capture both information demand and unresolved uncertainty, which has implications for the interpretation of common empirical tests involving such proxies. Controlling for the uncertainty that motivates information gathering is a potential approach for addressing this endogeneity issue. However, my findings indicate that firm-specific information gathering reflects unique information about firm-level investor uncertainty not captured by common controls for uncertainty. Analyses that exploit plausibly exogenous variation in information gathering suggest a promising direction for future research.